The Duality of a Dynamic Model of Equilibrium and an Optimal Growth Model: The Heterogeneous Capital Goods Case - Becker, Robert A. (Quarterly Journal of Economics, 1981)
The equivalence between optimal growth solutions and solutions of decentralized models of intertemporal allocation is explored in a one-consumer, heterogeneous capital goods framework. The decentralized economy follows a perfect foresight path. The main result is that the decentralized economy will impose on itself a transversality condition. This yields the interpretation of equilibrium prices as prices consistent with a certainty version of the efficient markets hypothesis. The results rest on the recent contribution by Benveniste and Scheinkman providing sufficient conditions for infinite horizon concave programs to exhibit capital value transversality as a necessary condition for optimality.